فقہ اسلامی کی روشنی میں تجارت: جدید مصطلحات ، ضوابط، اور شرعی ہدایات: Trade in the light of Islamic Jurisprudence: Modern Terms, Regulations, and Shariah Guidance (Al-Qamar, 2023)
This research paper explores the fundamental terminology, rules, and Islamic Shariah guidance concerning trade, as derived from Islamic jurisprudence. Trade is an integral part of economic activities, and understanding its principles within an Islamic context is essential for Muslims engaged in commercial transactions. The paper aims to provide a comprehensive overview of the key aspects of trade, including its definition, importance, and ethical considerations. The research methodology employed is primarily based on an extensive review of Islamic legal texts, including the Quran, Hadith and works of renowned Islamic jurists. Islamic Fiqah is the principle of the guidance of this world till last Day of Judgment. The section on basic terminology establishes a foundational understanding of trade by defining key terms such as 'buying' and 'selling,' 'profit,' 'goods,' and 'contracts.'.  The concept of 'Halal' (permissible) and 'Haram' (prohibited) goods and transactions is also explored, shedding light on the types of products or activities that are considered morally and legally acceptable or prohibited in Islamic trade.  It highlights the need for Muslims to be well-versed in the basic terminology, rules, and Shariah guidance pertaining to trade to ensure compliance with Islamic ethics and achieve both material success and spiritual fulfillment. This Article focuses over such issues and seek help from these Fiqah books in Order to get Devine wisdom in solving worldly issues.
Keywords: Trade; Islamic jurisprudence; terminology; Islamic Shariah guidance; economic activities; Interpretation